2017
DOI: 10.1364/optica.4.000643
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared continuous-wave parametric amplification in chalcogenide microstructured fibers

Abstract: The persistent growth of interest in the middle infrared (MIR) is stimulating the development of sources and components. Novel waveguides and fibers for the efficient use of nonlinear effects in the MIR are being intensively studied. Highly nonlinear silica fibers have enabled record performances of highly versatile parametric processes in the telecommunication band. However, no waveguiding platforms (to our knowledge) have yet solved the trade-off among high nonlinearity, low propagation losses and dispersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 38 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…Parametric conversion performed at a room temperature of 7°C showed no change on retrieved dispersion. The rotation of the input lens fiber showed a hole-pitch ratio variation within 2%, in accordance with the previous measurement [19]. Thus, we conclude that the ChG vapor that traveled through the air holes was deposited on their walls, effectively shrinking the size of the air hole.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Parametric conversion performed at a room temperature of 7°C showed no change on retrieved dispersion. The rotation of the input lens fiber showed a hole-pitch ratio variation within 2%, in accordance with the previous measurement [19]. Thus, we conclude that the ChG vapor that traveled through the air holes was deposited on their walls, effectively shrinking the size of the air hole.…”
supporting
confidence: 91%
“…For pulsed applications, an all-fiber MIR optical parametric oscillator [16], a parametric wavelength converter [17], and an allfiber MIR supercontinuum source [18] became feasible. For CW laser applications, advances in fabrication technology now allow for amplified parametric conversion in MIR [19], power delivery [20], and integration into the silica fiber network [21]. In CW applications, power intensities have exceeded 5 MW∕cm 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To shift the ZDW of 1st PCF structure at 2 µm wavelength so as to overcome the large material dispersion of AsSe glass, which has a ZDW around at 7 µm, the ratio d/Λ needs to be increased at 0.8 which enhances the fabrication difficulty of that design. Xing et al [52,53] reported a small core PCF design made of GeAsSe ChG glass for parametric conversions by shifting the PCF dispersion near the 2 µm region through micro-structuring and tapering the fiber while maintaining d/Λ ratio at ∼ 0.7. It was possible to obtain the ZDW with a lower d/Λ ratio for GeAsSe material owing to its lower material dispersion as compared to AsSe glass.…”
Section: Resultsmentioning
confidence: 99%
“…A chalcogenide PCF taper was proposed to increase the waveguide nonlinearity for wavelength conversion based on four-wave mixing (Le et al, 2012). Xing (Xing et al, 2017) used a 1-m-long tapered GeAsSe PCF fiber with a core diameter of 1.5 mm to achieve continuous-wave-pumped four-wave mixing by combining high nonlinearity, low dispersion, low loss, and single-mode behavior, which benefits from the engineered GeAsSe PCF structure. Figure 5 shows the schematic of the dispersion-engineered tapered GeAsSe PCF fiber.…”
Section: Four-wave Mixingmentioning
confidence: 99%